Manoeuvring prediction of offshore supply vessel - Che Wan Othman, Che Wan Mohd. Noor (2009)
International Maritime Organization (IMO) standard for ship manoeuvrability have hastened the need for more accurate prediction of ship's manoeuvrability at the early design stage. There are many methods available for manoeuvring prediction such as free running model test, captive model test and etc, however these methods are expensive and time consuming. As alternative the numerical simulation method with parameters determined from a database is taking place the current principal approach. This thesis presents a manoeuvring prediction of Offshore Supply Vessel (OSV) which includes the development of the time domain simulation programme. As being OSV, manoeuvring ability is very critical aspect in order to avoiding collision and grounding especially in harbour and offshore operations such as tow and tug. Thus, early prediction of OSV manoeuvring characteristic is essentially important. Manoeuvring time domain simulation programmed was developed by using Matlab Simulink software. Hydrodynamic derivatives and coefficients are calculated from proven Kijima formulae and then be incorporated to the simulation program. Prediction vessel swept paths were obtained by double integrating acceleration in surge, sway and yaw axis. Validation of the prediction results were carried out by comparing with full-scale sea trial results. It is found that some discrepancy to the prediction results can be improved by relative sensitivity studies on simulation parameters. The result of improved prediction tool shows a good agreement to the sea trial results. Hence manoeuvring prediction by numerical approximate formula is reliable and economic to be used as a prediction tool in early design stage.